Local regulation between formal and informal institutions: Analysis by application to the case of the town of Ksar-Hellal (Tunisia) - Makram Gaaliche (Atlantic Review of Economics, 2013)
The purpose of this paper is to detect the relevance degrees of formal and informal institutions at the level of local regulation, as well as their effects on the local companies' productivities. Indeed, by an analysis of the territory of the Ksar-Hellal town, we noted that informal institutions, apprehended by the trust and the collective punishment, contribute beside the formal penal institutions to channel the behaviors of the hilalian companies but with a less effectiveness. Similarly, the strong contribution of exogenous institutions in boosting productivity compared to that endogenous, states that the decision makers should improve the quality of formal regulation, and this at the expense of any form of regulation built by values commonly shared by the local community.
Keywords: O12; K20; L51; 330; local regulation; formal institutions; informal institutions; productivity; Tunisia